2016
DOI: 10.1016/j.brainresbull.2015.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of individual differences in the rat nucleus accumbens transcriptome following taste-heroin extended access

Abstract: Heroin addiction is a disease of chronic relapse that harms the individual through devaluation of personal responsibilities in favor of finding and using drugs. Only some recreational heroin users devolve into addiction but the basis of these individual differences is not known. We have shown in rats that avoidance of a heroin-paired taste cue reliably identifies individual animals with greater addiction-like behavior for heroin. Here rats received 5 min access to a 0.15% saccharin solution followed by the opp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…We have found only one gene from the ephrin receptor family, Epha3, which was down-regulated in the NAc of oxycodone-treated mice. In other studies, similar down regulation in the expression of ephrin genes in the rat NAc was observed at 24 h after secession of heroin self-administration (6 h/day for 5 days) ( 12 ). In contrast, cocaine treatment increased expression of many ephrin and ephrin receptor in the rat and mouse striatum and hippocampus ( 14 , 7 ) and in striatum of nonhuman primates ( 46 ).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…We have found only one gene from the ephrin receptor family, Epha3, which was down-regulated in the NAc of oxycodone-treated mice. In other studies, similar down regulation in the expression of ephrin genes in the rat NAc was observed at 24 h after secession of heroin self-administration (6 h/day for 5 days) ( 12 ). In contrast, cocaine treatment increased expression of many ephrin and ephrin receptor in the rat and mouse striatum and hippocampus ( 14 , 7 ) and in striatum of nonhuman primates ( 46 ).…”
Section: Discussionsupporting
confidence: 72%
“…Previously, microarray studies of morphine-treated mice showed alterations in expression of genes related to the semaphorin pathway in the NAc such as Sema3f, Sema4b, sema6c, Sema6d, Sema7a, and Plxna3 ( 10 ) and Sema6a ( 44 ). Heroin self-administration induced downregulation of Sema5a, Sema6c and receptor Plxnb1 in the rat NAc ( 12 ). Consistent with these earlier reports, in this study we have found oxycodone-induced downregulation of Sema3c, Sema4g, Sema6a, Sema6d, and upregulation Sema7a in the mouse NAc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average read after filtering was 50,021,043 ± 12,710,549, and the sequencing depth was 1,495. The RNA‐sequencing (RNA‐Seq) data analysis and principal component analysis were conducted as previously described . Sequence data were submitted to the Sequence Read Archive.…”
Section: Methodsmentioning
confidence: 99%
“…In so doing, they reported that greater avoidance of the heroin-paired saccharin cue was accompanied by not only greater drug-seeking and taking, but also by greater escalation of drug-taking over time. Here, Imperio et al [in this issue] link these individual differences in behavior to individual differences in the expression profile of a range of genes in the nucleus accumbens via next generation gene sequencing. McFalls et al [in this issue] examine how such individual differences in avoidance of the heroin-paired saccharin cue are associated with individual differences in the expression of genes in the corticotrophin releasing hormone (CRH) signaling pathway in the prefrontal cortex, hippocampus, ventral tegmental area, and nucleus accumbens.…”
Section: Addiction and Devaluation Of Natural Rewardsmentioning
confidence: 99%